Absence of Regeneration in the MRL/MpJ Mouse Heart Following Infarction or Cryoinjury - Robey, Thomas E. (2007)
The MRL/MpJ mouse has been reported to exhibit minimal scarring and subsequent cardiac regeneration after cryoinjury of the right ventricle. We studied the temporal evolution of infarcts and cryoinjuries in MRL/MpJ and C57BL/6 control mice. Both types of injury in MRL/MpJ mice heal similarly to controls by typical scar formation rather than muscle regeneration, and no differences in cell proliferation, angiogenesis or scar contraction between the two mouse strains were observed. BACKGROUND: Myocardial infarcts in mammals heal by scar formation rather than formation of new muscle tissue. The MRL/MpJ mouse, however, has been reported to exhibit minimal scarring and subsequent cardiac regeneration after cryoinjury of the right ventricle. Other groups have reported that permanent and temporary ligation of the coronary artery resulted in scarring without regeneration. METHODS: To clarify these contradictory results, we studied the temporal evolution of infarcts in MRL/MpJ and C57BL/6 control mice from 1 to 90 days post-injury, and the effects of intrathoracic cryoinjury to 28 days. RESULTS: After infarction, the conversion from necrotic myocardium to granulation tissue and then to scar proceeded identically in the two groups. Infarct DNA synthesis, measured by incorporation of a BrdU pulse, peaked at 4 days in both strains and did not differ between strains at any time point. Endothelial cell and total vascular density in the both the infarcted and non-infarcted cardiac tissue did not differ between groups at any time. Histological analysis of directly cryoinjured right and left ventricular myocardium showed indistinguishable wound healing in both strains, and final scar size was identical in each group. CONCLUSIONS: These studies demonstrate that both myocardial infarcts and cryoinjuries in MRL/MpJ mice heal by typical scar formation rather than muscle regeneration, in a manner very similar to C57BL/6 controls. We conclude that the MRL mouse is not a model for myocardial regeneration.